The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17041199
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Orientation, Green Supply Chain Management, and Firm Performance: Empirical Evidence from Chinese Small and Medium-Sized Enterprises

Abstract: This study investigates the relationship between environmental orientation and firm performance with the mediating role of green supply chain management (GSCM). This study uses a survey questionnaire to collect data from 247 CEOs from Chinese small and medium-sized enterprises (SMEs). Structural equation modeling is used to analyze data and test hypotheses. Empirical results show that internal and external environmental orientations are positively related to the three elements of GSCM, namely, environmental se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 48 publications
2
45
0
3
Order By: Relevance
“…The results of the study indicated that GSCM initiatives positively influenced the development of a strong and positive corporate image. These findings were also supported by [81]. Hence, it can be concluded that green supply chain management is an important factor that is a key predictor of green corporate image.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The results of the study indicated that GSCM initiatives positively influenced the development of a strong and positive corporate image. These findings were also supported by [81]. Hence, it can be concluded that green supply chain management is an important factor that is a key predictor of green corporate image.…”
Section: Discussionsupporting
confidence: 57%
“…The results suggested that the green marketing initiatives taken by the firms led to the development of a green corporate image. Moreover, Bu et al (2020) also analyzed the impact of environmental orientation on a firm's performance and concluded by saying that the green environmental initiatives undertaken by a firm positively influence its overall performance and solidify its brand presence in the market [81]. According to signal theory, the hotel is the sender of signals and the consumers are the receivers of the signals [11].Therefore, it can be concluded that the green marketing orientation activities of the firm play a critical role in the development of a green corporate image.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GSCM is a new field that tries to eliminate some of the traditional supply chain weaknesses like environmental efficiency (Chin et al , 2015; Rasi et al , 2012). GSCM follows the same activities but in a different way that is more profitable, innovative and widely acceptable, socially and pro-environmentally (Bu et al , 2020). GSCM is considered as an environmental innovation (Chin et al , 2015) which is often used for a variety of activities of the organization to reduce its impact on the natural environment, including the goal of inventory waste within the industrial system to conserve energy, prevent waste of hazardous substances in the environment and recognize the inappropriate environmental impact of supply chain operations within the organization (Shou et al , 2018).…”
Section: Introductionmentioning
confidence: 99%